PENERAPAN METODE GUIDED INQUIRY PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN RUANG SISI LENGKUNG UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Suryani, Lina (Kadikma, 2022)
This research is motivated by students who do not understand the concept of learning mathematics and student learning completeness is still low. The aim of the research was to increase the activity and learning outcomes in the Constructed Space Construct material using the guided inquiry method. The research subjects were class IX-D students of SMP Negeri 3 Balung. Actions include the teacher's ability to design lesson plans, implementation of learning, and observation in order to determine the increase in student learning outcomes. In the pre-cycle, it was known that the average learning outcomes were 76.10 and the learning completeness only reached 68.97% with a completeness score of 75. The results showed that there was an increase in student learning outcomes after the action was taken. In the first cycle, an average score of 77.4 was obtained and the learning completeness was 75.86%. In the second cycle, an average score of 81.90 was obtained and the learning completeness reached 89.65%, which means that learning mastery had been achieved.